The Underexploited Role of Non-Coding RNAs in Lysosomal Storage Diseases - Queiroz, Matheus Trovão de; Pereira, Vanessa Gonçalves; do Nascimento, Cinthia Castro; D’Almeida, Vânia (Frontiers in Endocrinology, 2016)
Non-coding RNAs (ncRNAs) are a functional class of RNA involved in the regulation of several cellular processes which may modulate disease onset, progression, and prognosis. Lysosomal storage diseases (LSD) are a group of rare disorders caused by mutations of genes encoding specific hydrolases or non-enzymatic proteins, characterized by a wide spectrum of manifestations. The alteration of ncRNA levels is well established in several human diseases such as cancer and auto-immune disorders; however, there is a lack of information focused on the role of ncRNA in rare diseases. Recent reports related to changes in ncRNA expression and its consequences on LSD physiopathology show us the importance to keep advancing in this field. This article will summarize recent findings and provide key points for further studies on LSD and ncRNA association.